(untitled) (Communication & Society, 2012)
This paper examines internal pluralism in the governance of public service broadcasters in Spain, a dimension of pluralism on which very little research has been done in this country. In particular, it analyses the role played by social groups and professionals in the management structures of Spanish public service broadcasters through their participation in the advisory councils and professional councils of such media. Because of its importance, the case of RTVE is discussed at length.